Psychological Status of Orthodontic Patients During Covid-19 Pandemic and its Impact on their Treatment Process: Psychological Status of Orthodontic Patients During Covid-19 Pandemic - Tahmasbi, Soodeh; Namdari, Mahshid; Dalaie, Kazem; Behnaz, Mohammad; Seif Zargar , Aminhesam; Nilgaran, Reyhaneh (Journal of Dental School, 2024)
Objectives The present study aimed to investigate the patients’ psychological status, level of awareness, and attitude toward the coronavirus disease 2019 (COVID-19) pandemic and its effects on the process of orthodontic treatment in patients at the School of Dentistry, Shahid Beheshti University of Medical Sciences, and three private clinics in the city of Tehran in 2021-2022. Methods A questionnaire with four parts was designed. The participant’s general information and the information regarding orthodontic treatments were collected in the first part, and the patient’s knowledge and attitude in confronting COVID-19 were collected in the next two parts. In the last part, the patient’s psychological status was assessed using Kessler’s Psychological Distress Scale (K10). A total of 300 questionnaires were distributed among the patients in four clinics. Spearman’s correlation coefficients, the t-test, and U Mann-Whitney statistical test were used at a significance level of 0.05. Results A total of 209 patients undergoing fixed orthodontic treatment participated in the present study. The mean score of the K10 questionnaire among the participants was 11.93. 30.14% of the participants could not attend their orthodontic appointments at least once during 6 months. 59.8% of the participants reported much concern about going to the dental office and contracting a disease. 25.8% of patients were worried about falling brackets, loosening bands, and breaking wires during the outbreak. On the other hand, 69.8% had no problem in contacting their orthodontist. Conclusion Most patients had no missed orthodontic appointments during 6 months, and more than a quarter believed that COVID-19 had affected their orthodontic treatments. The patients’ psychological status was not suitable especially in women. In general, with higher educational level, the awareness of COVID-19 increased, and the psychological status worsened.